2012
DOI: 10.4025/actasciagron.v34i1.11979
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence among maize hybrids and correlations with heterosis and combining ability

Abstract: ABSTRACT. Twelve corn hybrids recommended for cropping in the south-central region of the Paraná State and 66 crossings obtained among these hybrids were evaluated for agronomic and morphological traits. These genotypes were evaluated in three experiments performed in Laranjeiras do Sul, Guarapuava and Cantagalo, Paraná State, Brazil. Heterosis and specific combining ability (SCA) were estimated for yield of husked ears. Data from measuring 22 morphological/agronomical traits of the parents were subjected to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
3
5
0
5
Order By: Relevance
“…A divergência entre os genitores pode ser associada à variação observada entre as médias para as três características avaliadas (Tabelas 3, 4 e 5), porém apenas a divergência genética não é suficiente para assegurar elevados níveis de heterose (OLIBONI et al, 2012). A CEC se manifesta em função dos efeitos de dominância e epistasia e das diferenças nas frequências alélicas dos genitores para os locos envolvidos no controle de determinada característica (HALLAUER; CARENA; MIRANDA FILHO, 2010).…”
Section: Resultsunclassified
“…A divergência entre os genitores pode ser associada à variação observada entre as médias para as três características avaliadas (Tabelas 3, 4 e 5), porém apenas a divergência genética não é suficiente para assegurar elevados níveis de heterose (OLIBONI et al, 2012). A CEC se manifesta em função dos efeitos de dominância e epistasia e das diferenças nas frequências alélicas dos genitores para os locos envolvidos no controle de determinada característica (HALLAUER; CARENA; MIRANDA FILHO, 2010).…”
Section: Resultsunclassified
“…A elevada CEC observada é resultante da manifestação dos genes de efeitos não aditivos em cruzamentos entre indivíduos geneticamente divergentes (FUZATTO et al, 2002;OLIBONI et al, 2012).…”
Section: Resultsunclassified
“…However, the authors suggest that extreme genetic distance data should be used for the choice of more promising crosses once the best hybrids have been obtained by the combination of lines with bigger genetic distances. Oliboni et al (2012) evaluated genetic divergence among 12 corn hybrids used as genitors in a complete diallel scheme, and did not observe significant positive correlations between genetic distance and the genetic parameters used in the formation of base populations. They concluded that genetic divergence is not sufficient to account for the heterosis observed in hybrids once the occurrence of heterosis also depends on the degree of dominance of the considered characteristic.…”
Section: Genetic Divergence and Correlationsmentioning
confidence: 95%
“…Oliboni et al (2012) estimated genetic distance using multivariate techniques with genetic parameters obtained for diallel crosses between commercial corn hybrids. These authors affirmed that such techniques are important tools for understanding heterotic groups in corn breeding programs, and they contribute to the prediction of promising crosses and the formation of improved base populations.…”
Section: Genetic Divergence and Correlationsmentioning
confidence: 99%